2014
DOI: 10.1186/1746-1596-9-124
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of primary T-cell lymphoblastic lymphoma: description of two cases

Abstract: BackgroundT-cell lymphoblastic lymphoma comprises approximately 85-90% of all lymphoblastic lymphomas. It often arises as a mediastinal mass, and with bone marrow involvement. Presentation at other sites without nodal or mediastinal localization is uncommon.Case reportWe describe clinical, histologic, immunohistochemical, and molecular features of two cases of primary T-cell lymphoblastic lymphoma arising respectively in uterine corpus and testis. The tumors were composed by medium to large cells, exhibiting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In addition, the skin, tonsils, lymph nodes, liver, spleen, central nervous system, and male testes may also be invaded by tumor cells. [ 12 ] This case at beginning was diagnosed as T-LBL, but ended as MPAL. Honestly, there are some limitations about this case, for instance, bone marrow puncture was not performed in the beginning, so we have no idea whether the bone marrow was invaded or not?…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the skin, tonsils, lymph nodes, liver, spleen, central nervous system, and male testes may also be invaded by tumor cells. [ 12 ] This case at beginning was diagnosed as T-LBL, but ended as MPAL. Honestly, there are some limitations about this case, for instance, bone marrow puncture was not performed in the beginning, so we have no idea whether the bone marrow was invaded or not?…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have reported atypical presentations of T-cell leukaemia/lymphoma such as variable oral lesions [ 11 ] or cutaneous manifestations [ 16 ] in patients with ATL, renal infarction subsequent to polyarteritis nodosa in a patient with angioimmunoblastic T-Cell lymphoma [ 17 ], and testicular and uterine mass lesions in two patients with T-cell lymphoblastic lymphoma [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides these tumors, rosettes rarely occur in lymphoma, endometrial stromal sarcoma and osteosarcoma . Here, we discuss a case of meningioma showing rosettes with collagenous cores.…”
Section: Introductionmentioning
confidence: 99%